2007
DOI: 10.1089/ten.2006.0210
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Bioactive Insulin from Human Epidermal Keratinocytes and Tissue-Engineered Skin Substitutes: Implications for Treatment of Diabetes

Abstract: Despite many years of research, daily insulin injections remain the gold standard for diabetes treatment. Gene therapy may provide an alternative strategy by imparting the ability to secrete insulin from an ectopic site. The epidermis is a self-renewing tissue that is easily accessible and can provide large numbers of autologous cells to generate insulin-secreting skin substitutes. Here we used a recombinant retrovirus to modify human epidermal keratinocytes with a gene encoding for human proinsulin containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Our earlier studies revealed that insulin stimulates keratinocyte migration and proliferation and regulates keratinocyte differentiation (6,21,22). Moreover, previous studies suggest that hyperglycaemia and decreased insulin signals are involved in impairment of skin function (23–25). Therefore, the distorted keratinocyte phenotypes in diabetics may be a major factor in endogenous skin lesions and delayed wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies revealed that insulin stimulates keratinocyte migration and proliferation and regulates keratinocyte differentiation (6,21,22). Moreover, previous studies suggest that hyperglycaemia and decreased insulin signals are involved in impairment of skin function (23–25). Therefore, the distorted keratinocyte phenotypes in diabetics may be a major factor in endogenous skin lesions and delayed wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy has also been considered to achieve permanent restoration of insulin production [174]: studies in this field confirmed the possibility of obtaining ectopic insulin production from different cells, for example, keratinocytes or fibroblasts [175,176] using ex vivo gene transfer methods. Using in vitro techniques, gene transfer genetically modified cells in vitro, then they are transplanted into the subjects: in animal models, this approach allowed a secretion of insulin able to promote glucose uptake and normalize glycemia.…”
Section: Gene Therapymentioning
confidence: 99%
“…This could be an aid to industrial fabrication of keratinocytes sheet in the 3D structure for skin tissue engineering. Some recent study have shown the genetic modification in the keratinocytes for overexpression of important protein encoding genes like high expression of platelet derived growth factor gene modified keratinocytes sheet for the high vasucalarization potential in vivo [164], overexpression of vascular endothelial growth factor using cationic liposomes for high reepithilization potential of keratinocytes with increased production of ECM [165], expression of human proinsulin gene for the active secretion of insulin from the skin tissue, which promote the uptake of glucose and could be used as an alternative technique for the tretment of diabetes [166].…”
Section: Skin Tissue Engineeringmentioning
confidence: 99%